Perioperative Approach in a Patient with Myasthenia Gravis - Kuci, Saimir; Ibrahimi, Alfred; Memeti, Shaban; Goga, Marsela; Dumani, Selman; Refatllari, Ali (Scientific Foundation SPIROSKI, 2021)
Background: Myasthenia gravis is an autoimmune neuromuscular disorder that causes the destruction and overall decrease in functional acetylcholine receptors at the neuromuscular junction. The resultant respiratory and cardiovascular implications are a primary cause of mortality; therefore, a complete and comprehensive understandings of this disorder is vital for the anesthesia provider. Anesthesia management in myasthenia gravis is a great challenge for all anesthesiologists. In this disease, even small doses of muscle relaxants could lead to delayed recovery for respiratory muscles. Case report: We present the case of a 38 years old woman (weight 87 kg) diagnosed with Myasthenia Gravis, which symptoms has worsened recently. The case demonstrates the anesthetic challenges involved, with a focus on the overall approach, pharmacologic considerations, physiological changes, and an emphasis on preoperative operative and post-operative optimization. Conclusion: Thymectomy is a common procedure performed in cases of myasthenia gravis (MG) with a thymoma or general MG that does not improve with medical therapy. During anesthesia the use of propofol or sevoflurane with opioids without the use of any neuromuscular blocking agents has been used with success.